PENDIDIKAN KELUARGA: Integrasi Ayat-Ayat Al Quran pada Pengembangan Potensi Santri - Amaliyah, Amaliyah; Latifah, Siti; Merdeka, Muhamad; Sanjaya, Riyan (Jurnal PKM Manajemen Bisnis, 2025)
This community service activity was driven by the need to integrate Qur’anic values into the educational process of santri (Islamic boarding school students), particularly in shaping character and developing their spiritual, intellectual, and social potential. The activity was conducted by students of class MPIK001 from the Islamic Education Management (MPI) undergraduate program at Universitas Pamulang (UNPAM) at Nurul Hidayah Islamic Boarding School, Bojongsari, Depok. A total of 87 participants were involved, consisting of 7 lecturers, 7 boarding school teachers, 22 students, and 50 santri. The main objective of this program was to strengthen the understanding and implementation of Qur’anic verses in the daily lives of santri and to enhance awareness of self-potential development based on Islamic values. The implementation used the expository learning model, enabling participants to actively comprehend the concepts and practical applications of Qur’anic integration through direct explanation, discussion, and reflection. The results showed increased enthusiasm and understanding among santri regarding the importance of the Qur’an as a guide for personal development. Additionally, the activity fostered collaboration between pesantren management and university students in designing educational strategies based on Qur’anic principles.